149k views
2 votes
Which equation is y = –6x^2 + 3x + 2 rewritten in vertex form? y = negative 6 (x minus 1) squared + 8 y = negative 6 (x + one-fourth) squared + thirteen-eighths y = negative 6 (x minus one-fourth) squared + nineteen-eighths y = negative 6 (x minus one-half) squared + seven-halves

User Nktssh
by
5.6k points

2 Answers

6 votes

Answer:

C. y = -6 (x-1/4 )^2 +19/18

Step-by-step explanation: right on edge

User CodingYoshi
by
5.1k points
4 votes

Answer:

y = negative 6 (x minus one-fourth) squared + nineteen-eighths/ C on edg

Explanation:

User Felix Quehl
by
5.9k points